2022
DOI: 10.1183/13993003.00611-2022
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes of bronchiectasis in India: data from the EMBARC/Respiratory Research Network of India registry

Abstract: IntroductionIdentifying risk factors for poor outcomes can help with risk stratification and targeting of treatment. Risk factors for mortality and exacerbations have been identified in bronchiectasis but have been almost exclusively studied in European and North American populations. This study investigated the risk factors for poor outcome in a large population of bronchiectasis patients enrolled in India.MethodsThe EMBARC-India registry is a prospective observational study of adults with CT confirmed bronch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 31 publications
1
9
0
Order By: Relevance
“…Although it had a small sample size, the US study found that 44% of patients used PEP devices and 10% used HFCWO at baseline, in contrast to our European data where only 16% used devices and HFCWO was not used in most European countries, and the country with the highest use only had a frequency of 1.9%. These data emphasise global variation in practice, likely reflecting differences in reimbursement practices as well as lack of availability of specialist chest physiotherapists in many countries [ 24 , 32 ]. It should be noted that, while we had a large sample size overall, the numbers in individual countries varied.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although it had a small sample size, the US study found that 44% of patients used PEP devices and 10% used HFCWO at baseline, in contrast to our European data where only 16% used devices and HFCWO was not used in most European countries, and the country with the highest use only had a frequency of 1.9%. These data emphasise global variation in practice, likely reflecting differences in reimbursement practices as well as lack of availability of specialist chest physiotherapists in many countries [ 24 , 32 ]. It should be noted that, while we had a large sample size overall, the numbers in individual countries varied.…”
Section: Discussionmentioning
confidence: 99%
“…Bronchiectasis is a heterogeneous disease and mucus properties are highly heterogeneous between individuals. It is important that future studies generate a more robust evidence base for ACT in addition to identifying appropriate precision medicine approaches [ 3 , 24 , 33 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…EMBARC is a prospective observational study of patients with computed tomography (CT)-confirmed bronchiectasis conducted across more than 30 countries worldwide [ 13 , 14 ]. The registry includes European Union (EU) countries, non-EU European countries and several non-European countries (Israel, India, Kyrgyzstan and Pakistan) [ 14 , 15 ]. The study is approved by the ethical committee in the host country (UK) and by institutional review boards or ethics committees in all countries and regions in which the study is conducted.…”
Section: Methodsmentioning
confidence: 99%
“…Bronchiectasis is a chronic respiratory disease where people suffer ongoing symptoms of cough, sputum production and frequent respiratory infections, leading to progressive lung function decline and reduced quality of life [1][2][3] . The disease is defined by abnormal, permanent dilation of the bronchi resulting in impaired clearance of mucus from the airways.…”
Section: Introductionmentioning
confidence: 99%